2001
DOI: 10.1038/sj.leu.2402029
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic subgroups in acute myeloid leukemia differ in proliferative activity and response to GM-CSF

Abstract: The current study was undertaken to search for differences in the biology of cytogenetic subgroups in patients with de novo acute myeloid leukemia (AML). In addition, factors influencing the metabolism of cytosine arabinoside (araC) as the key agent of antileukemic activity were assessed. Bone marrow aspirates from 91 patients with newly diagnosed AML in whom karyotypes were successfully obtained were analyzed: (1) for spontaneous proliferative activity by 3 H-thymidine ( 3 H-TdR) incorporation; (2) proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…High levels correlated with poor response to chemotherapy [56,57] and short duration disease free survival [56,58] . Contrasting results were obtained in another study where spontaneous proliferative determined by tritiated thymidine incorporation was significantly higher in favourable karyotypes compared to cases with unfavorable cytogenetics [59] .…”
Section: Abdullah M Unapplied Markers In Amlcontrasting
confidence: 69%
See 2 more Smart Citations
“…High levels correlated with poor response to chemotherapy [56,57] and short duration disease free survival [56,58] . Contrasting results were obtained in another study where spontaneous proliferative determined by tritiated thymidine incorporation was significantly higher in favourable karyotypes compared to cases with unfavorable cytogenetics [59] .…”
Section: Abdullah M Unapplied Markers In Amlcontrasting
confidence: 69%
“…Proliferative activity of AML blasts were significantly higher in favourable karyotypes compared to unfavourable karyotypes. Exposure to GM-CSF significantly increased proliferation in normal and unfavarouble groups compared to favourable karyotype [59] . CD34+ expression of cells from AML bone marrow were significantly reduced following incubation with a cytokine mix without affecting viability in all samples analysed.…”
Section: Abdullah M Unapplied Markers In Amlmentioning
confidence: 92%
See 1 more Smart Citation
“…This is important, since chemoresistance mediated by both of these mechanisms is potentially amenable to modulation, which could lead to significant improvements in clinical outcome. Further evidence supporting the notion that karyotype analysis identifies subgroups of AML that are biologically similar irrespective of the age of the patient has been provided by recent studies reporting a close correlation between cytogenetic subgroup and bax/bcl2 ratio, 31 immunophenotypic profile, 32 and the behavior of primary leukemic blasts, both in vitro, in terms of proliferative activity, semisolid colony growth, and response to granulocyte-macrophage colony-stimulating factor, 33,34 and in vivo, influencing engraftment characteristics in nonobese diabetic/ severe combined immunodeficient mice. 35 To date, cytogenetic classification systems used to predict outcome in AML have been somewhat inconsistent.…”
Section: Discussionmentioning
confidence: 82%
“…The group with favorable cytogenetics benefits more from cytarabine dose escalation in induction therapy (Burnett AK et al Br J Haemtol 1996; 93(Suppl 2): 313; abstract) [59][60][61] and from HDAC in consolidation therapy. 62,63 Jahns et al 64 reported the findings of cell-cycle studies of the blast cells from different cytogenetic risk groups. 64 Blast cells from patients with a favorable karyotype had a high level of spontaneous proliferative activity and were not responsive to growth stimulatory cytokines, while blasts from most patients with an unfavorable karyotype had a low level of spontaneous proliferative activity and were sensitive to HGF growth stimulation.…”
Section: Discussionmentioning
confidence: 99%